2012
DOI: 10.1111/j.2047-2927.2012.00005.x
|View full text |Cite
|
Sign up to set email alerts
|

Relations of morphometric parameters to zinc content in paediatric and nonhyperplastic young adult prostate glands

Abstract: SUMMARYTo clarify age-related histological and zinc content changes in paediatric and nonhyperplastic young adult prostate glands, a quantitative morphometric and energy-dispersive X-ray fluorescence analysis (EDXRF) was performed. The prostates were obtained at autopsy from 50 subjects (European-Caucasian aged 0-30 years) who died from sudden infant death syndrome, acute pulmonary aetiologies and trauma. None of the subjects had any symptoms of prostatic disease and all prostates were classified as histologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
41
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 29 publications
0
41
0
Order By: Relevance
“…It was also found that the percent volumes of these histological structures depend from age and the individual uroflowmetric characteristics of the subject [68]. Moreover, the variations of the individual percent volumes of histological structures and uroflowmetric characteristics also increase with age [24,67,68].…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…It was also found that the percent volumes of these histological structures depend from age and the individual uroflowmetric characteristics of the subject [68]. Moreover, the variations of the individual percent volumes of histological structures and uroflowmetric characteristics also increase with age [24,67,68].…”
Section: Discussionmentioning
confidence: 91%
“…This conclusion followed from the qualitative analysis of individual data sets [24,38,53,[65][66][67]. It was also found that the percent volumes of these histological structures depend from age and the individual uroflowmetric characteristics of the subject [68].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In our previous studies a significant involvement of Zn, Ca, Mg, and, perhaps, Rb and some other trace element in the function of prostate was observed [12][13][14][15][16][17][18][19][20][21][22]. One of the main functions of prostate gland is a produc- intercourse for 3 days preceding the procedure.…”
Section: Introductionmentioning
confidence: 99%
“…The reason for the unusually high trace element content in normal prostate gland is not completely understood. The findings of low Zn level in pediatric prostate warranted the conclusion that androgens are the major factors controlling the accumulation and maintenance of a high content of Zn in the prostate [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%